Trends in overweight and obesity in children under 24 months of age in Mexico (2012-2020): analysis of four national health surveys - Velia Margarita Cárdenas-Villarreal; Lucia Hernandez-Barrera; Danilo Castro-Sifuentes; Milton Carlos Guevara-Valtier; Belem Trejo-Valdivia (Cadernos de Saúde Pública, 2023)
Abstract: The prevalence of childhood obesity has increased rapidly in Mexico, with significant consequences for the population’s health in the future. Little is known about the prevalence of obesity in children under two years of age, even though this life stage is fundamental to prevent this condition. This study aims to determine the magnitude, distribution, and trends of overweight and obesity in children under 24 months of age using the Mexican National Health and Nutrition Surveys (ENSANUT) conducted in the last 10 years. The data presented here are derived from four ENSANUTs, carried out in Mexico in 2012, 2016, 2018, and 2020. They include 6,719 infants under 24 months with complete anthropometric data (weight/height) by age, gender, Indigeneity, area of residence, and socioeconomic status. The risk of overweight levels and overweight + obesity rates were calculated according to World Health Organization guidelines. We identified that infants < 12 months currently have a higher prevalence of overweight + obesity (10.3%) and that those aged 12 to 23 months are generally at a higher risk of overweight (26.1%). The most relevant findings of this study, linking weight trends to sex, region, socioeconomic status, and indigeneity, show that overweight and obesity prevalences vary across the Mexican population, without presenting a specific behavior. There is a high prevalence of overweight and obesity among Mexican infants and a slight trend toward increased obesity in infants < 12 months. Weight monitoring and obesity prevention interventions focused on the first 1,000 days of life are essential.